(untitled) (Research, Society and Development, 2021)
Brazil is the world’s largest producer of sugarcane, so the aim of this work was to present the economic, social and environmental impacts of its cultivation, and, to show some applications of the by-products generated in the production process with a focus on the sustainability of the sector. The methodology used was the literature review, available in four databases: Scielo, CAPES, Science Direct and Google Scholar on the topic. It can be seen that the sugar and alcohol industry have an impact on both the economic, social and environmental sectors. By-products from processing when well used can promote profits, reduce environmental problems and generate jobs and income. However, it is necessary to invest more in the public and private sectors in technologies and academic research, since the use of by-products is highly promising for sustainable development, allowing the correct destination of the waste generated, leading to the promising path of sustainable development.